Education on Processing Cow's Milk into Various Flavors to Enhance the Appeal of Educational Tourism in Babadan Village: Edukasi Pengolahan Susu Sapi Menjadi Susu Berbagai Rasa untuk Meningkatkan Daya Tarik Wisata Edukasi di Desa Babadan - Hayati, Anis Khoirin; Adi, Ali; Imaniah, Anissa Alifia; Kartika, Mas Aldrin Zagna Rania; Ornando, Muhammad Athallah Hazel; Wulandari, Yunita (Journal of Empowerment and Community Service (JECSR), 2023)
Milk is an important source of nutrition that is rich in protein, fat, vitamins, minerals and probiotic microorganisms. However, the high nutrient content also increases the risk of microbial growth that can cause spoilage if not handled properly. One method to extend the shelf life of milk is through the pasteurization process. Babadan Village, located on the slopes of Mount Kelud, has great potential in the dairy farming sector as the main source of community income. However, there is still a lack of understanding about hygienic and innovative milk processing. This research aims to increase awareness of safe milk processing techniques and diversification of dairy-based products in Babadan Village to support the local economy and educational tourism. The methods used include coordination with stakeholders, observation in the field, and education through hands-on practice of milk processing with various flavors. This activity involved UMSIDA Group 1 KKN-P 2025 students and local elementary school students in understanding the importance of pasteurization, sterilization, and dairy product innovation. The results of the activity showed an increased understanding of the community, especially elementary school students, about the importance of good milk processing to increase product durability and selling value. This program also has the potential to increase the attractiveness of educational tourism in Babadan Village, which is expected to have a positive impact on the community.